2023
DOI: 10.3390/medicina59030527
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Status and Oxidative Stress in SARS-CoV-2 Patients

Abstract: Background and Objectives: Insufficient intake of essential micronutrient selenium (Se) increases the susceptibility to diseases associated with oxidative stress. The study aim was to assess Se status and oxidative stress in COVID-19 patients depending on severity of the disease. Materials and Methods: Blood plasma of 80 post-COVID-19 disease patients and 40 acutely ill patients were investigated. Concentration of Se was detected by a fluorometric method with di-amino-naphthalene using acidic hydrolysis. Selen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Elevated levels of lipid peroxidation products in patients infected with the SARS-CoV-2 were also reported in other studies. 6 , 63 , 64 Some researchers found correlations between the concentrations of lipid peroxidation products and disease severity, 65 and between 4-HNE levels and the risk of mortality in COVID-19 patients. 6 The peroxidation of lipids, mainly unsaturated fatty acids, leads to the production of peroxides and, in subsequent reactions, aldehydes such as MDA and HNE 66 , 67 which were analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of lipid peroxidation products in patients infected with the SARS-CoV-2 were also reported in other studies. 6 , 63 , 64 Some researchers found correlations between the concentrations of lipid peroxidation products and disease severity, 65 and between 4-HNE levels and the risk of mortality in COVID-19 patients. 6 The peroxidation of lipids, mainly unsaturated fatty acids, leads to the production of peroxides and, in subsequent reactions, aldehydes such as MDA and HNE 66 , 67 which were analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Lowered selenium in plasma correlates with decreasing tolerance to viral infection, induced ROS formation, which leads to oxidative stress. It induces cell and tissue damage [27] and can weaken the immune system in total [28]. Plasma selenium level was determined using the Alfthan fluorometric method, based on the reduction of selenium compounds at an excitation wavelength of 369 nanometers and an emulsion wavelength of 518 nanometers (previously reported [27]).…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…It induces cell and tissue damage [27] and can weaken the immune system in total [28]. Plasma selenium level was determined using the Alfthan fluorometric method, based on the reduction of selenium compounds at an excitation wavelength of 369 nanometers and an emulsion wavelength of 518 nanometers (previously reported [27]). Reference values are 70 to 130 µg/L [29].…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…Circulating and excretory MDA concentrations have been determined in COVID-19 patients and used as a biomarker of oxidative stress [26][27][28][29][30][31][32][33][34]. Of these articles, only one study reported on age-dependency of circulating MDA [34].…”
Section: Malondialdehyde In Covid-19 41 Malondialdehyde In Acute Long...mentioning
confidence: 99%
“…Šk , esters and colleagues [30,31] measured MDA in the plasma of 120 COVID-19 patients (age not reported) by means of a commercially available OxiSelect™ TBARS (MDA Quantitation) assay kit. The MDA plasma concentration was reported to be 27 ± 11 µM in 40 acutely ill COVID-19 patients, 31 ± 19 µM in 40 post-COVID-19 patients in the springsummer wave, and 27 ± 11 µM in 40 post-COVID-19 patients in the summer-autumn wave (no year reported).…”
Section: Malondialdehyde In Covid-19 41 Malondialdehyde In Acute Long...mentioning
confidence: 99%